Preparation of tannin–formaldehyde–furfural resin with pretreatment of depolymerization of condensed tannin and ring opening of furfural. Issue 9 (2nd May 2016) - Yi, Zhao; Wang, Wen; Zhang, Wei; Li, Jianzhang
Abstract: As renewable and economical bio-based resources, tannin can polymerize with aldehyde to form resin, furfural can partially substitute formaldehyde for the preparation of resin with phenols. Aiming to enhance the reaction efficiency between tannin and furfural by weakening the steric hindrance, a pretreatment was applied to depolymerize the macromolecule of tannin into small one and open the furan ring structure of furfural before the preparation of tannin–formaldehyde–furfural (TFFu) resin. Modified furfural was used to partially substitute formaldehyde by the ratios of 10, 20, and 30%. Chemical structure characteristics, thermal behaviors, dynamic viscosity, and fracture surface micrograph of the TF and TFFu resins were analyzed by Fourier transform infrared spectroscopy, differential scanning calorimetry and thermogravimetric analysis, rheological measurement, and scanning electron microscopy, respectively. The result indicated that co-polycondensation with modified furfural decreased the free formaldehyde content of TFFu resin, and increased the thermal stability. Moreover, when the formaldehyde was substituted by modified furfural in 10%, the TFFu resin had the most smooth and compact fracture surface.